Between us : how cultures create emotions - Mesquita, Batja, ....- (New York : W.W. Norton & Company, 2022)
"How are you feeling today?" We may think of emotions as universal responses, felt inside, but in Between Us, acclaimed psychologist Batja Mesquita asks us to reconsider them through the lens of what they do in our relationships, both one-on-one and within larger social networks. From an outside-in perspective, readers will understand why pride in a Dutch context does not translate well to the same emotion in North Carolina, or why one's anger at a boss does not mean the same as your anger at a partner in a close relationship. By looking outward at relationships at work, school, and home, we can better judge how our emotions will be understood, how they might change a situation, and how they change us. Brilliantly synthesizing original psychological studies and stories from peoples across time and geography, Between Us skillfully argues that acknowledging differences in emotions allows us to find common ground, humanizing and humbling us all for the better.
Keywords: Emoties